1998
DOI: 10.1037/0278-7393.24.4.1041
|View full text |Cite
|
Sign up to set email alerts
|

Slow and steady often ties the race: Effects of item-specific and relational processing on cumulative recall.

Abstract: Analysis of cumulative recall curves originally led to the conclusion that asymptotic recall is inversely related to the rate of approaching asymptote. This finding suggests that recall differences between conditions on a short test would continue to exist with longer tests. However, this assumption is not always correct. In Experiments 1 and 2, orienting tasks promoting relational processing produced an initial recall advantage over item-specific processing tasks, but the advantage diminished by the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
2
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(69 citation statements)
references
References 40 publications
2
62
2
3
Order By: Relevance
“…To help us better conceptualize the differences between the two learning methods, we defined them in terms of a framework of differential processes that occur inherently due to the different learning methods. Specifically, it was expected that relational processing would occur for both repeated study and repeated retrieval in the learning of a categorized word list (Burns & Hebert, 2005;Burns & Schoff, 1998;Rundus, 1971), but repeated study would lend itself to more item-specific processing of materials due to increased exposure time and the creation of distinctive memory traces. While this combination of processing was expected to yield superior immediate recall, the operation of some item-specific processing was also deemed likely to interfere with the processing of information relationally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To help us better conceptualize the differences between the two learning methods, we defined them in terms of a framework of differential processes that occur inherently due to the different learning methods. Specifically, it was expected that relational processing would occur for both repeated study and repeated retrieval in the learning of a categorized word list (Burns & Hebert, 2005;Burns & Schoff, 1998;Rundus, 1971), but repeated study would lend itself to more item-specific processing of materials due to increased exposure time and the creation of distinctive memory traces. While this combination of processing was expected to yield superior immediate recall, the operation of some item-specific processing was also deemed likely to interfere with the processing of information relationally.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that cumulative recall curves are effective in revealing the separate and/or mixed influences of item-specific and relational processing inherent in a participant's recall (Burns & Hebert, 2005;Burns & Schoff, 1998). Specifically, item-specific processing is characterized by curves where recall of studied material is both slower initially and slower to reach asymptotic level of recall, thereby producing a slow, steady rate across the entire recall period.…”
Section: Cumulative Recall and Cumulative Organization Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptotic recall level and rate of approaching asymptote have consistently been found to be inversely related, such that higher levels of asymptotic recall produce a slower approach to asymptote (see, e.g., Bousfield & Sedgewick, 1944;Herrmann & Chaffin, 1976;Herrmann & Murray, 1979;Johnson, Johnson, & Mark, 1951;Kaplan, Carvellas, & Metlay, 1969). However, Burns and Schoff (1998) showed that this relationship is often violated when differing levels of item-specific and relational processing are performed. The curves typically produced following item-specific, relational, or both types of processing have been published in several places (Burns, 2006;Burns & Hebert, 2005;Burns et al, 2006;Burns & Schoff, 1998), so we will not reproduce them here.…”
mentioning
confidence: 96%
“…A decrease in item losses results from enhanced relational processing, apparently because the encoded relational information provides an organized search strategy that facilitates accessibility of the items (see Burns & Gold, 1999;Burns & Schoff, 1998;Hunt & McDaniel, 1993;McDaniel, Moore, & Whiteman, 1998). Presumably, the same relational cues are used across successive tests, resulting in a similar retrieval strategy that minimizes item losses.…”
mentioning
confidence: 99%